Multitargeted biological actions of polydatin in preventing pseudogout acute attack - Baggio, Chiara; Galozzi, Paola; Damasco, Amelia; Lazzarin, Vanni; Ravagnan, Giampietro; Sfriso, Paolo; Ramonda, Roberta; Punzi, Leonardo; Pennelli, Gianmaria; Doria, Andrea; Luisetto, Roberto; Oliviero, Francesca (Frontiers in Molecular Biosciences, 2025)
IntroductionWe have recently shown that polydatin (PD) prevents calcium pyrophosphate (CPP) crystal-induced arthritis in mice. This study aims to explore potential mechanisms of action associated with this anti-inflammatory effect.Materials and methodsAcute arthritis was induced in Balb/c mice by the injection of crystals into the ankle joint. Animals were randomised to receive PD or colchicine according to a prophylactic protocol. Ankle swelling was measured and both joints and muscles were harvested at sacrifice. Histological evaluations were performed using H&E staining to assess cartilage and muscle damage. Kondziela’s inverted test was used to assess muscle strength. An exploratory protein array was performed on joint tissue to identify relevant inflammatory pathways. Human monocytes pretreated with PD were stimulated with CPP crystals. The use of specific inhibitors was instrumental in demonstrating their anti-inflammatory effects and assessing the role of SIRT1. The chemotaxis assay was performed to test the effect of PD and J-113863 on PBMCs migration in response to plasma and synovial fluids. Cytokine levels were measured by ELISA.ResultsCPP crystals injection resulted in swelling, leukocyte infiltration, loss of synovial membrane structure homogeneity. Mice pretreated with PD showed reduced ankle swelling and this was associated with very limited inflammatory damage. Regarding the effect on gastrocnemius muscle, crystals induced leukocyte infiltration and edema. PD and colchicine treatment reduced muscle damage and preserved musculoskeletal structure in mice. The cytokine array revealed the activation of various inflammatory pathways after CPP injection and PD was shown to influence leukocyte migration, angiogenesis and inflammation. In vitro, PD reduced inflammatory cytokines, chemokines and VEGF levels. CCR-1 inhibition was effective in reducing pro-inflammatory mediator levels in CPP treated monocytes and in reducing PBMCs migration. The anti-inflammatory action of PD also involved SIRT-1 activation, and its inhibition reverted the beneficial effects of PD. Finally, PD reduced the PBMCs migration in response to synovial fluids.ConclusionPD effectively prevents inflammatory responses to CPP crystals in mice, preserving both articular and muscular structures. Its anti-inflammatory effects are primarily mediated through pathways regulating leukocyte migration and the suppression of pro-inflammatory mediators.